DETEKSI KEBERADAAN BAKTERI RESISTEN LOGAM MERKURI (Hg) PADA PENAMBANGAN EMAS TANPA IZIN (PETI) DI SIMPI, SEKADAU, KALIMANTAN BARAT - Abdullah Abdullah (Indonesian Journal of Pure and Applied Chemistry, 2018)
The purpose of this research is to know the existence of mercury metal degradation bacteria in the activity of illegal gold mining (PETI) in Simpi Village, Belitang Hilir sub-district, Sekadau District, West Kalimantan. The samples were taken from one location with three different sampling points. Isolation of bacteria by pour plate method  in NA-HgCl medium. Detection of bacteria by paper disc method based on inhibit zone resistant of  Mueller-Hinton Agar (MHA) with mercury levels such as 10 mg/L, 20 mg/L and 30 mg/L . The results showed that it was found that one pure isolate (PP) showed the most resistant isolate to the mercury stress of 10 mg/L can be detected